Solving linear system of partial differential equations by homotopy-pertubation method - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak; Ismail, Ahmad Faris (2009)
In this paper, the homotopy-perturbation method (HPM) is employed to obtain approximate analytical solution to the linear systems of partial differential equations (PDEs). HPM yields solutions in convergent series forms with easily computable terms, and in linear cases, yields exact solutions. Comparisons with the exact solutions show the potential of HPM in solving linear systems of PDEs.